Coinfection of Sexually Transmitted Infections among HIV-Positive Individuals: Cross-Sectional Results of a Community-Based Positive Living with HIV (POLH) Study in Nepal. (July 2017) - Poudel, Krishna C.; Poudel-Tandukar, Kalpana; Palmer, Paula H.; Mizoue, Tetsuya; Jimba, Masamine; Kobayashi, Jun; Acharya, Bishnu; Pandey, Basu Dev; Oka, Shinichi
In Asian concentrated HIV epidemics, data on coinfection of sexually transmitted infections (STIs) among HIV-positive individuals are limited. The authors measured the prevalence of Chlamydia trachomatis (CT), Neisseria gonorrhea (NG), and syphilis, and their correlates among 319 HIV-positive individuals in Kathmandu, Nepal. The authors tested blood samples for syphilis and urine samples for CT and NG. Overall, 17 (5.3%) participants had at least 1 STI (CT: 1.3%, NG: 2.8%, and syphilis: 1.2%). Of 226 participants who had sex in past 6 months, 51.3% did not always use condoms. Older (aged 35-60 years) participants were more likely (adjusted odds ratio [AOR] = 3.83; 95% confidence interval [CI] = 1.19-12.33; P = .024) and those who were currently married (AOR = 0.30; 95% CI = 0.09-0.97; P = .046) or on antiretroviral therapy (AOR = 0.21; 95% CI = 0.06-0.71; P = .012) were less likely to have at least 1 STI. Our results suggest the need to strengthen the efforts to screen and treat STIs and to promote safer sexual practices among Nepalese HIV-positive individuals.